Buyer power and suppliers' incentives to innovate - Christian Köhler; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Buyer power is widely considered to decrease innovation incentives of suppliers. However, there is little empirical evidence for this statement. Our paper analyses how buyer power influences innovation incentives of upstream firms while taking into account the type of competition in the downstream market, namely price and technology. We explore this relationship empirically for a unique dataset containing 1,129 observations of German firms from manufacturing and service sectors including information on the economic dependency of firms from their buyers. Using a generalised Tobit model, we find a negative effect of buyer power on a supplier's likelihood to start R&D activities. This negative effect is mitigated if the supplier faces powerful buyers operating under strong price competition. There is also weak evidence for a negative effect of buyer power on suppliers' R&D intensity if the powerful buyer operates under strong technology competition.
Keywords: L11; O31; 330; Innovation; Buyer Power